RESILIENCE AS A PREDICTOR OF POST-TRAUMATIC GROWTH AMONG SOLDIERS WOUNDED IN COMBAT AT 44 NIGERIAN ARMY REFERENCE HOSPITAL, KADUNA. - Yusuf Gbenga, Rafiu (African Journal of Social and Behavioural Sciences, 2025)
Military operations expose soldiers to various stressors and traumatic events, which can often lead to negative psychological outcomes such as Post-Traumatic Stress Disorder (PTSD), depression, and anxiety. However, some soldiers experience Post-Traumatic Growth (PTG), demonstrating positive changes despite adversity. This study aimed to examine the role of resilience in contributing to PTG among Nigerian soldiers wounded in action. Using a cross- sectional survey design and purposive sampling, 109 male wounded-in-action soldiers were selected from the 44 Nigerian Army Reference Hospital in Kaduna. Resilience was measured using the Brief Resilience Scale, and PTG was measured using the Post-Traumatic Growth Inventory. Results showed that resilience (β = .321, p = .004) significantly predicted PTG. Specifically, resilience was a significant predictor of PTG, F(1, 105) = 8.76, p = .004, R² = .103, indicating that resilience accounted for 10.3% of the variance in PTG. Although this R² value is relatively low, it suggests that resilience, while significant, may not be the sole factor influencing PTG, and other variables may contribute to these outcomes. The study concluded that resilience is a key factor in promoting PTG among wounded-in-action soldiers. Based on these findings, it is recommended that the military develop and implement comprehensive resilience-building activities among deployed soldiers.